P53 TRANSCRIPTION FACTOR AND DIABETES: IS THERE ANY LINK? - Murtaza, Imtiyaz (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Diabetes, a metabolic disorder is alarmingly increasing across the globe and currently ample of research is being carried out to treat hyperglycaemia and its secondary complications in diabetic patients. Despite extensive research, specific causes of this metabolic disorder are still not well understood at molecular level. As p53 a tumor suppressor gene has mostly been associated with cancer, however, the most recent research studies sheds light on vital role of p53 signalling in diabetes development. In this review we underline the role of altered p53 protein expression in diabetes and its associated metabolic disorders including hypertension and dyslipidemia. We try to throw some light on latest studies that suggest how p53 signalling may act as a new potential therapeutic target for diabetes and its related metabolic disorders.